2022
DOI: 10.1108/ecam-05-2022-0469
|View full text |Cite
|
Sign up to set email alerts
|

The influence of higher learning institutions in developing the experience economy from the perspective of the urban community

Abstract: PurposeThe development of higher learning institutions (HLIs) is considered a strategy to trigger urban space development – and it is the economy in most developing countries. HLIs can develop and maintain pace with the experience economy in the current urban economy, particularly in the services sector. This paper seeks to evaluate the influence of HLIs on elements of the experience economy in the urban services sector in Bandar Baru Bangi (BBB), a knowledge-based city.Design/methodology/approachThe research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…Bilsland et al (2019) identified inadequate stakeholder collaboration as a potential hindrance to internship value. The stakeholder in this context includes the local HEI, intern work supervisors and the internship placement (Nor Azazi et al, 2022). Lax government agency apprenticeships oversight, inadequate legislation, social and cultural perceptions and funding challenges are possible drawbacks of apprenticeship (Decker, 2019).…”
Section: The Built Environment Craftmanshipmentioning
confidence: 99%
“…Bilsland et al (2019) identified inadequate stakeholder collaboration as a potential hindrance to internship value. The stakeholder in this context includes the local HEI, intern work supervisors and the internship placement (Nor Azazi et al, 2022). Lax government agency apprenticeships oversight, inadequate legislation, social and cultural perceptions and funding challenges are possible drawbacks of apprenticeship (Decker, 2019).…”
Section: The Built Environment Craftmanshipmentioning
confidence: 99%